2013
DOI: 10.1111/jocn.12519
|View full text |Cite
|
Sign up to set email alerts
|

Managing medications: the role of informal caregivers of older adults and people living with dementia. A review of the literature

Abstract: Aims and objectives To explore published literature that describes what is known about the role of informal caregivers as they manage medications for older adults and/or people living with dementia residing in the community. Background The number of informal caregivers of older adults, including people living with dementia, is growing worldwide. Good medication management by informal caregivers contributes to improved health outcomes and reduced institutionalisations for the care recipient; however, little is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 27 publications
3
119
0
4
Order By: Relevance
“…102 In addition, carers felt that they received inadequate support in planning their relatives' care, that their contribution to managing their relatives' care was not always recognised and that they were often excluded from decision-making. A systematic review 153 investigating the role of informal caregivers of PLWD found that family carers are often expected to manage medication regimens, the complexity of which are increasing. However, health-care systems and structures were often not helpful, for example family caregivers might not be included in communications about medication regimen changes and were not given the information and support that they needed to carry out their medication management roles.…”
Section: Views and Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…102 In addition, carers felt that they received inadequate support in planning their relatives' care, that their contribution to managing their relatives' care was not always recognised and that they were often excluded from decision-making. A systematic review 153 investigating the role of informal caregivers of PLWD found that family carers are often expected to manage medication regimens, the complexity of which are increasing. However, health-care systems and structures were often not helpful, for example family caregivers might not be included in communications about medication regimen changes and were not given the information and support that they needed to carry out their medication management roles.…”
Section: Views and Experiencesmentioning
confidence: 99%
“…Seven 72,92,102,125,132,148,162 were qualitative studies, one 107 was a mixed study including a review and a qualitative study, three 93,99,153 were reviews and two 20,94 were questionnaire studies. Three studies 20,94,102 focused on people with dementia and diabetes, two 72,93 focused on those with dementia and VI, one 89 looked at those with dementia and deafness, one 92 focused on those with dementia and cancer, two 148,153 looked at family carers' views on medication management and four 99,107,125,132 looked at the needs of people with dementia in general hospitals. Literature on the experiences of older people with dementia in acute general hospitals has highlighted shortcomings in the care provided, the attitudes and training of staff, and the physical environment and problems with care cultures.…”
Section: Views and Experiencesmentioning
confidence: 99%
“…Having an informant for each participant would also be useful to ensure that, if the intervention is pharmacological, it is taken in adherence with the protocol, as medication management can be difficult for people with dementia, and often caregivers provide support. 479,480 Informants are also often involved in the completion of outcomes on behalf of the person with dementia they care for. There was discussion around who completes outcomes at both the PPI consultation and consensus conference and, although it is important that people with dementia should be enabled to complete measures, informal carers also need to be involved.…”
Section: Recommendations Around Completing Outcomesmentioning
confidence: 99%
“…While caregiving may provide rewards (Lloyd, Patterson, & Muers, 2014; Roth, Fredman, & Haley, 2015), caregivers’ responsibilities increase over time (Alzheimer’s Association, 2017; Gillespie, Mullan, & Harrison, 2014; Spillman, Wolff, Freedman, & Kasper, 2011), adversely affecting caregivers’ health (Fonareva & Oken, 2014), psychological and social well-being (Schulz & Martire, 2004); and family relationships (Gaugler, Zarit, & Pearlin, 1999; Tremont, Davis, & Bishop, 2006). Although few are trained for this work, caregivers essentially play the role of a clinician and even a healthcare team.…”
Section: Introductionmentioning
confidence: 99%